Collecting High Frequency Panel Data in Africa Using Mobile Phone Interviews - Hoogeveen, Johannes (Taylor and Francis, 2014)
As mobile phone ownership rates have risen in Africa, there is increased interest in using mobile telephony as a data collection platform. This paper draws on two pilot projects that use mobile phone interviews for data collection in Tanzania and South Sudan. In both cases, high frequency panel data have been collected on a wide range of topics in a manner that is cost effective, flexible and rapid. Attrition has been problematic in both surveys, but can be explained by the resource and organizational constraints that both surveys faced. We analyze the drivers of attrition to generate ideas for how to improve performance in future mobile phone surveys.